Cervical Pessary and Vaginal Progesterone in Twin Pregnancies With a Short Cervix. Issue 4 (April 2016) - Fox, Nathan S.; Gupta, Simi; Lam-Rachlin, Jennifer; Rebarber, Andrei; Klauser, Chad K.; Saltzman, Daniel H.
Abstract : OBJECTIVE: To evaluate cervical pessary as an intervention to prevent preterm birth in twin pregnancies with a short cervix. METHODS: This was a retrospective cohort study of twin pregnancies managed by a single maternal-fetal medicine practice from 2005 to 2015. We included patients at 28 weeks of gestation or less who were diagnosed with a cervical length less than 20 mm. At the time of diagnosis, all patients were prescribed vaginal progesterone. Starting in 2013, they were also offered pessary placement in addition to vaginal progesterone. We compared outcomes between patients who received a pessary and matched women in a control group in a one-to-three ratio. Women in the control group were matched to women in the case group according to cervical length and gestational age (within 5 mm and 1 week, respectively, of the case patient at the time of pessary placement). We excluded patients with cerclage, monochorionic–monoamniotic placentation, major fetal congenital anomalies discovered before or after birth, patients with twin-twin transfusion syndrome, and patients for whom there were no appropriate controls. Chi-square, Fisher exact, and Student's t tests were used, as appropriate. Regression analysis was performed to control for significant differences at baseline. RESULTS: Twenty-one patients received a cervical pessary, and they were compared with 63 matched women in the control group. As expected (as a result of matching), baseline gestational age (25.7±2.1 compared with 25.9±2.1 weeks of gestation, P =.671) and cervical length (10.9±3.6 mm compared with 11.9±4.5 mm, P =.327) were similar between the groups. Patients with a pessary had a significantly lower incidence of delivery at less than 32 weeks of gestation (1/21 [4.8%] compared with 18/63 [28.6%], adjusted P =.05), longer interval to delivery (65.2±16.8 compared with 52.1±24.3 days, adjusted P =.025), and a lower incidence of severe neonatal morbidity (2/21 [9.5%] compared with 22/63 [34.9%], adjusted P =.04). CONCLUSION: For twin pregnancies with a short cervix, the addition of a cervical pessary to vaginal progesterone is associated with prolonged pregnancy and reduced risk of adverse neonatal outcomes. A large randomized trial should be performed to verify these retrospective findings. Abstract : In twin pregnancies with a short cervical length, cervical pessary is associated with prolonged pregnancy and reduced risk of adverse neonatal outcomes.